European Respiratory Society statement on sleep apnoea, sleepiness and driving risk. Issue 2 (25th February 2021) - Bonsignore, Maria R.; Randerath, Winfried; Schiza, Sofia; Verbraecken, Johan; Elliott, Mark W.; Riha, Renata; Barbe, Ferran; Bouloukaki, Izolde; Castrogiovanni, Alessandra; Deleanu, Oana; Goncalves, Marta; Leger, Damien; et al.
Obstructive sleep apnoea (OSA) is highly prevalent and is a recognised risk factor for motor vehicle accidents (MVA). Effective treatment with continuous positive airway pressure has been associated with a normalisation of this increased accident risk. Thus, many jurisdictions have introduced regulations restricting the ability of OSA patients from driving until effectively treated. However, uncertainty prevails regarding the relative importance of OSA severity determined by the apnoea–hypopnoea frequency per hour and the degree of sleepiness in determining accident risk. Furthermore, the identification of subjects at risk of OSA and/or accident risk remains elusive. The introduction of official European regulations regarding fitness to drive prompted the European Respiratory Society to establish a task force to address the topic of sleep apnoea, sleepiness and driving with a view to providing an overview to clinicians involved in treating patients with the disorder. The present report evaluates the epidemiology of MVA in patients with OSA; the mechanisms involved in this association; the role of screening questionnaires, driving simulators and other techniques to evaluate sleepiness and/or impaired vigilance; the impact of treatment on MVA risk in affected drivers; and highlights the evidence gaps regarding the identification of OSA patients at risk of MVA. Drivers with obstructive sleep apnoea and sleepiness are at risk of driving accidents; this is removed by effective therapy, and recent European regulations have been implemented on this topic https://bit.ly/3mXDhV1